Case Report: Upper extremity deep vein thrombosis revealing an occult invasive ductal breast carcinoma - Chiorescu, Stefan; Oiegar, Ruxandra; Mocan, Mihaela; Trif, Mihaela; Ciocan, Razvan Alexandru; Chiorescu, Roxana Mihaela (Frontiers in Cardiovascular Medicine, 2026)
Deep vein thrombosis of the upper limb is a rare but clinically significant condition, as it may represent the first manifestation of an underlying malignancy and often poses diagnostic and therapeutic challenges. We present the case of a 66-year-old woman with no significant medical history, admitted for extensive deep vein thrombosis of the left upper limb that developed shortly after surgical decompression of the carpal tunnel. Postoperatively, she presented with marked swelling of the left arm, and Doppler ultrasonography confirmed thrombosis of the deep venous system. Thoracic computed tomography illustrated tumoral infiltration of the left subclavian vein and artery, causing segmental venous thrombosis and severe arterial stenosis. Despite elevated serum levels of the tumor marker Cancer Antigen 15-3, both mammography and breast ultrasonography were negative. A thoracic computed tomography–guided biopsy established the diagnosis of invasive lobular breast carcinoma, Nottingham grade 1, estrogen receptor–positive, with Ki-67 < 5%. Staging procedures included positron emission tomography combined with computed tomography, magnetic resonance imaging of the breast, and confirmatory breast biopsy. The particularity of this case lies in its atypical onset, initially mimicking carpal tunnel syndrome, combined with upper limb venous thrombosis caused by an occult breast tumor undetectable by conventional imaging but infiltrating the axillary vascular bundle. Therapeutic decisions followed international guidelines for cancer-associated thrombosis, with anticoagulation tailored to bleeding risk and oncologic therapy individualized according to the tumor's immunologic profile. ConclusionsUpper extremity deep vein thrombosis is frequently associated with malignancy and may represent its first clinical manifestation, as in our patient, whose axillary breast carcinoma invaded the arteriovenous structures without detectable breast lesions. Early recognition of this condition is essential for timely diagnosis and improved prognosis. Direct oral anticoagulants represent a valuable therapeutic option with multiple advantages. Their potential antineoplastic effects—particularly those of factor XI inhibitors currently under investigation—may provide additional benefits in cancer-associated thrombosis.